Effect of Indomethacin on Blood Pressure Managed by Captopril and Losartan in Hypertensive Patients - Sabeen Arjumand, Fareeha, Liaqat Ali, Gul E Nazish, Zarish Ghafoor, Maira Bhatti (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Determine the role of indomethacin on blood pressure lowering by captopril and losartan in hypertension patients. Study design: Randomized study design. Methodology: 200 patients with known hypertension problems including women and men were treated in this study. The complete protocol for the study was approved by the research center and committee of the hospital. Patients were randomly treated with losartan 50mg/day, and captopril 25mg two times/day. . Indomethacin 65 mg /day was given to patients in week six. Results: Among the 200 patients 68 (50%) females received losartan and 68 (50%) females received captopril. Captopril was given to a total of 100 patients including 68 females and 32 males. Their first-week follow-up systolic BP Mean ± S.E measured value was 152.02 ± 0.9, Diastolic BP measured value was 94.5 ± 0.5, Pulse, bpm = 86.6 ± 2.0 with a significant p-value. The fifth week measured reading was 141.04 ± 0.7 = systolic BP, 86.05 ± 1.2 = Diastolic BP, Pulse, bpm = 86.6 ± 2.0. A significant reduction in BP was observed with a p-value of 0.001. At sixth-week captopril and indomethacin combination results show a lesser reduction in BP systolic/ diastolic = 146.06 ± 0.2/89.01 ± 2.0 mm Hg, pulse rate measured 81.7 ± 1.0 with significant p-value 0.05. Losartan first week follow-up shows a BP of 153.01 ± 0.3/92.6 ± 0.6, pulse reading was 79.3 ± 2.0 with a p-value of 0.001. In the fifth week, BP was 139.5 ± 0.1/ 84.03 ± 0.3, pulse = 77.6 ± 3.0 showing a significant reduction in BP. The sixth week Losartan + indomethacin results show a lesser decrease in BP with 145.4 ± 0.1/ 91.02 ± 0.4 mm Hg, and 79.01 ± 3.1 value was measured for Pulse, bpm. Conclusion: The results of this study show that losartan and captopril are more effective in controlling BP than in combination with indomethacin. So, indomethacin reduced the antihypertensive effect of losartan and captopril. Keywords: captopril, losartan, indomethacin, antihypertensive, blood pressure